PENGARUH MODEL PEMBELAJARAN MANDIRI TIPE MASTER SISWA KELAS VIII SMP N 22 MERANGIN - Novia Anggriani (Pendidikan Matematika | STKIP YM Bangko, 2019)
This research is motivated by the lack of understanding of students' mathematical concepts. From the seven indicators of understanding mathematical concepts, there are three indicators of understanding concepts that cannot be achieved by students. This type of research is an experimental study with a Posttest-Only Control Design research design. The sampling technique uses Simple Random Sampling. The population of this study was students of class VIII of SMPN 22 Merangin with samples of class VIII A as the experimental class and class VIII B as the control class. Data collection techniques in research using a description test understanding mathematical concepts. Data analysis techniques in hypothesis testing using the Mann-Whitney test (U test). Based on the research results the average value of the experimental class taught by the Master type independent learning model is 14.27 and the average control class taught by the conventional model is 11.76. Value < or then Ha is accepted and Ho is rejected. The conclusion of this research is the understanding of mathematical concepts taught using the Master type independent learning model is better than understanding mathematical concepts taught using conventional models in class VIII students of SMPN 22 Merangin.